Pengaturan Pengangkatan Perangkat Desa di Kabupaten Blitar - Weppy Susetiyo; Erwin Widhiandono; Anik Iftitah (Jurnal Supremasi, 2019)
This research departs from the subject matter of the arrangement of appointment of village officials in Blitar Regency after the expulsion of the domicile requirements of prospective village officials by the Constitutional Court of the Republic of Indonesia (Article 50 Paragraph 1 letter c) of Law Number 6 of 2014 concerning Villages) because it proved unconstitutional. To answer questions, it is used for normative legal research, draw conclusions about disharmony in the arrangement of appointment of village officials, and arrangements for the appointment of village officials in Kab. Blitar contains a substance that is not legal certainty.